Germany's new government and its foreign policy on Turkey: Lines of conflict and areas of cooperation - Günter Seufert (Stiftung Wissenschaft und Politik (SWP), 2021)
In stark contrast to Germany's Bundestag elections in 2017, Turkey has hardly been mentioned in this year's election campaign. Nevertheless, today's relatively relaxed atmosphere between Berlin and Ankara and the lack of prominence ascribed to their relationship in the German election campaign do not mean that shaping future foreign policy on Turkey will be an easy undertaking. Ankara is making a number of demands on the European Union (EU). Cooperation on refugee matters and efforts to deepen the customs union with the EU are to continue. The Turkish government also wants to be involved in European consultations. It is now up to Germany's new federal government to make its position known on these matters. However, Turkey is no easy partner to deal with and in order to achieve rules-based cooperation, Berlin and Brussels must, for their part, formulate clear conditions, for example, when it comes to cooperation on migration and defence. They also need to decide how to shape Turkey's future relationship with Europe.
Keywords: 320